2012
DOI: 10.1007/bf03262881
|View full text |Cite
|
Sign up to set email alerts
|

Association of anthropometric measures and dental caries among a group of adolescent cadets of Udupi district, South India

Abstract: There was a significant association between anthropometric measures and caries status in 15-19 years age group while no association was found in 12-14 years age group. Obesity and dental caries have common risk determinants and require a comprehensive multi-disciplinary approach by health care professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
1
4
1
Order By: Relevance
“…In our study, the percentage of overweight and obesity was 22.7 and 5.3%, respectively. Our observed prevalence was higher than that reported by Thippeswamy et al [17], but less than that reported by Chakravathy et al [18]. These differences were likely due to discrepancies between the definitions of overweight and obesity, age groups and genders selected for study, uniformity of the study sample, region in India, and methodology employed.…”
Section: Discussioncontrasting
confidence: 83%
“…In our study, the percentage of overweight and obesity was 22.7 and 5.3%, respectively. Our observed prevalence was higher than that reported by Thippeswamy et al [17], but less than that reported by Chakravathy et al [18]. These differences were likely due to discrepancies between the definitions of overweight and obesity, age groups and genders selected for study, uniformity of the study sample, region in India, and methodology employed.…”
Section: Discussioncontrasting
confidence: 83%
“…There was no signi cant difference between gender and the mean DMFT\dmft value which was found to be 1.9 ± 2.2 in 12-year-old children in the Study for Oral and Dental Health Pro le of Turkey (Gokalp et al, 2007). In parallel with this study, although there are other studies revealing that the mean DMFT in girls is higher (Koksal et al, 2011;Chakravathy et al, 2012), it was determined in some studies that oral and dental health indicators were similar by gender (Esa and Razak, 2001;Koposova et al, 2010;Adeniyi et al, 2016). It is stated that the prevalence of caries may be higher due to the earlier ages for dentition in girls and the emergence of periodontal problems due to hormonal changes in puberty period (Akinci, 2008).…”
Section: Discussionsupporting
confidence: 75%
“…Similarly to the above, there have been conflicting findings from studies in adolescent and child populations in India. Half of these studies observed no association, while the other half found a direct association, with more caries being reported in children who were obese or overweight. An important reason for the discrepancies, that also influences any comparison between the studies is non‐uniform BMI cut‐off values.…”
Section: Discussionmentioning
confidence: 99%
“…With this information, the SES of each family was evaluated using the Kuppuswamy scale, which is a composite instrument that has definite scoring criteria for occupation, education of the head of the household and family income 17 . Based on the composite score, the SES of the family was categorised as upper (score: [26][27][28][29], upper middle (score: [16][17][18][19][20][21][22][23][24][25], lower middle (score: [11][12][13][14][15], upper lower (score: 5-10) and lower (score: <5). As there were very few subjects in the upper (three subjects) and lower (one subject) categories, such subjects were included in the upper middle and upper lower SES categories, respectively.…”
Section: Methodsmentioning
confidence: 99%